2018
DOI: 10.1111/evo.13560
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of dispersal syndrome and its corresponding metabolomic changes

Abstract: Dispersal is one of the strategies for organisms to deal with climate change and habitat degradation. Therefore, investigating the effects of dispersal evolution on natural populations is of considerable interest to ecologists and conservation biologists. Although it is known that dispersal itself can evolve due to selection, the behavioral, life-history and metabolic consequences of dispersal evolution are not well understood. Here, we explore these issues by subjecting four outbred laboratory populations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 114 publications
(330 reference statements)
2
24
0
Order By: Relevance
“…S2 for fecundity at 24 h). Our findings in the one-generation experiment are similar to those of Tung et al (2018) in Drosophila melanogaster after several generations of selection for dispersal. They suggested that identical body size and fecundity despite the constitutive and induced costs of dispersal was offset by a shorter lifespan; our experiment was not designed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…S2 for fecundity at 24 h). Our findings in the one-generation experiment are similar to those of Tung et al (2018) in Drosophila melanogaster after several generations of selection for dispersal. They suggested that identical body size and fecundity despite the constitutive and induced costs of dispersal was offset by a shorter lifespan; our experiment was not designed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 81%
“…Among the few dispersal metabolomics studies published, van Petegem et al 2016found that more dispersive populations were characterized by lower concentrations in fructose, as well as lower activities of metabolic pathways associated with protein synthesis (as depicted by the lower amounts of a range of amino acids), the latter suggesting a reduced investment towards egg production in dispersive females. Meanwhile, Tung et al (2018) reported an increased aerobic metabolism (higher amounts of glucose AMP and NAD) in flies selected for enhanced dispersal abilities. These differences may be explained by dispersers investing more than residents in dispersal-related traits to mitigate dispersal costs, which may lead them to have fewer resources to allocate to reproduction and to stress resistance mechanisms (Bonte et al, 2012), especially if dispersal and stress responses share metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…For this experiment, we used VB (dispersal-selected) populations and their corresponding control and ancestral populations, VBCs ( [42,46], see electronic supplementary material, figure S3 and text S1.6). At the time of this study, these flies had undergone selection for dispersal for 70 generations.…”
Section: (Iii) Experiments 3: Evolutionary Dispersal Syndrome Under Stmentioning
confidence: 99%
“…In order to circumvent these issues, we used a different approach to assess the evolutionary dispersal syndrome. Like many other Drosophila life-history evolution experiments (for example, see [46,47]), we compared the VBs with their corresponding controls (VBCs), which have been maintained and evolved in parallel to these populations. Except for the selection for dispersal, the VBCs have undergone identical maintenance as the VBs (including the duration of desiccation stress faced by VBs during dispersal).…”
Section: (Iii) Experiments 3: Evolutionary Dispersal Syndrome Under Stmentioning
confidence: 99%
See 1 more Smart Citation